2017
DOI: 10.1177/0265407517705492
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in experiences of social support among men and women releasing from prison

Abstract: Objectives: Positive social support is critically important to postprison well-being outcomes. However, researchers and program developers are still trying to understand how to best promote stable and sustainable social support for formerly incarcerated individuals during reentry to the community. We sought to add to the body of knowledge on social support and prisoner reentry by comparing men and women releasing from prison on the quality (e.g., positive or negative) and amount of informal social support. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 57 publications
2
16
1
2
Order By: Relevance
“…For instance, female participants have been found to be less likely than their male counterparts to be rearrested following involvement in drug court programs (Spohn, Piper, Martin, & Frenzel, ), after post‐prison release drug treatment (Yang et al, ), and more likely to avoid arrest while on parole (Blackburn, Pfeffer, & Harris, ). Research on these gender differences has suggested many possible explanations for higher success rates among women under criminal justice supervision, including the presence of social support provided by family members and case managers (e.g., Holmstrom, Adams, Morash, Smith, & Cobbina, ; Pettus‐Davis, Veeh, Davis, & Tripodi, ). Literature on the gender paradox also suggests that women tend to demonstrate positive treatment outcomes despite the presence of a significant amount of risk factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, female participants have been found to be less likely than their male counterparts to be rearrested following involvement in drug court programs (Spohn, Piper, Martin, & Frenzel, ), after post‐prison release drug treatment (Yang et al, ), and more likely to avoid arrest while on parole (Blackburn, Pfeffer, & Harris, ). Research on these gender differences has suggested many possible explanations for higher success rates among women under criminal justice supervision, including the presence of social support provided by family members and case managers (e.g., Holmstrom, Adams, Morash, Smith, & Cobbina, ; Pettus‐Davis, Veeh, Davis, & Tripodi, ). Literature on the gender paradox also suggests that women tend to demonstrate positive treatment outcomes despite the presence of a significant amount of risk factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…among women under criminal justice supervision, including the presence of social support provided by family members and case managers (e.g.,Holmstrom, Adams, Morash, Smith, & Cobbina, 2017;Pettus-Davis, Veeh, Davis, & Tripodi, 2018). Literature on the gender paradox also suggests that women tend to demonstrate positive treatment outcomes despite the presence of a significant amount of risk factors (e.g Florentine, Anglin, Gil-Rivas, & Taylor, 1997),.…”
mentioning
confidence: 99%
“…Aunado a ello, se ha observado que son las mujeres quienes suelen establecer relaciones personales más cercanas (Juárez Ramírez, Valdez Santiago, & Hernández Rosete, 2005) en donde tienden a compartir más de su vida y emociones, evidenciando con eso su disposición a recibir ayuda, consejo, etc. (Matud, Ibañez, Bethencourt, Marrero, & Carballeira, 2003;Pettus-Davis, Veeh, Davis, & Tripodi, 2018).…”
Section: Discussionunclassified
“…In addition, forensic peers providing services report positive self-reflection as part of being able to "give back" (Baron, 2011) and increased self-esteem, prosocial behavior, and social connectedness (Heidemann, Cederbaum, Martinez, & LeBel, 2016). Forensic peer interventions may be especially important for justice-involved women compared to men, as women demonstrate an increased need for social support post-incarceration (Pettus-Davis, Veeh, Davis, & Tripodi, 2018;Valera, Chang, Hernández, & Cooper, 2015).…”
Section: Peer-supported Recovery For Justice-involved Womenmentioning
confidence: 99%